Early Real-World Patient and Staff Experience With an Intracanalicular Dexamethasone Insert [Corrigendum] - Nijm L; Matossian C; Rhee MK; Stephens JD; Rosselson ME; Majmudar PA; Gollamudi SR; Patel RH; Bauskar A; Montieth A; Vantipalli S; Gibson A; et al. (Clinical Ophthalmology)
Nijm L, Matossian C, Rhee MK, et al. Clin Ophthalmol. 2024;18:1391–1401. The authors have advised due to an error at the time of figure assembly, Figure 6A on page 1397 is incorrect. The correct minute should read 13.4 in “One Less Drop (DEXTENZA + 2 Drop Regimen)”. The correct Figure 6 is as follows.